Economia Internacional - Dasilva, Ricardo (Meridiano 47 - Journal of Global Studies, 2017)
Resenha de CARMO, Edgar Cândido; MARIANO, Jefferson (Orgs.). Economia Internacional. São Paulo: Saraiva, 2006,140p. ISBN: 97 88502060 88.